What Is a Science of Religion?. (21st September 2018) - Appiah, Kwame Anthony
Abstract: Modern sociology and anthropology proposed from their very beginnings a scientific study of religion. This paper discusses attempts to understand religion in this 'scientific' way. I start with a classical canon of anthropology and sociology of religion, in the works of E. B. Tylor (1832–1917), Max Weber (1864–1920) and Émile Durkheim (1858–1917). Science aims to be a discourse that transcends local identities; it is deeply cosmopolitan. To offer a local metaphysics as its basis would produce a discourse that was not recognizable as a contribution to the cosmopolitan conversation of the sciences. So, a science of religion cannot appeal to the entities invoked in any particular religion; hence the methodological atheism of these three founding fathers. This cosmopolitan ideal, the calling of the scientist, on the one hand, and the concern to understand the ideas of other cultures, on the other, can pull in different directions. Understanding requires us to appeal to our own concepts but not to our own truths. In the explanations, though, truth – the universal shared reality – has to matter, because the scientific story of religion has to work for people of all faiths and none, precisely because it is cosmopolitan. Not everything we call a religion will have historical Christianity's laser-like focus on ontological truth-claims. But as long as there are people making truth-claims in the name of religion, there will be the possibility of a tension between the very idea of a science of religion and some of the multifarious collections of beliefs, practices and institutions that make up what we now call 'religions'.